The Application of NPK Pearl Professional 9-25-25 on the Growth and Production of Red Bean Plants (Phaseolus vulgaris L.) in Lowlands - Andrew Fisher; Juniarny Silfana S. Waworuntu; Imanuel R. Montolalu (Jurnal Penelitian Pendidikan IPA, 2023)
This study aims to determine the application of NPK Pearl 9-25-25 on the growth and production of red bean plants (Phaseolus vulgaris L.) in lowlands. The research was conducted from February to May 2023 in Airmadidi, North Minahasa Regency, North Sulawesi at an altitude of 100 meters above sea level. They were using a Randomized Complete Block Design with the application of NPK Pearl 9-25-25 at 4 levels (0 g/liter of water, 2 g/liter of water, 4 g/liter of water, and 6 g/liter of water). The observed variables were plant height, number of branches, flowering age, number of pods, and net dry weight. The application of NPK Pearl 9-25-25 at a dose of 4 g/liter of water on the 45th day after planting (DAP) resulted in the tallest plant height of 47.80 cm, the highest number of branches with 18 branches, while the fastest flowering age was 30 DAP with doses of 4 g/liter of water and 6 g/liter of water, the highest number of pods was 33.60 pods, and the heaviest net dry seed weight per plant was 66 grams at a dose of 4 g/liter of water. The application of NPK Pearl 9-25-25 had a non-significant effect on plant height and the number of branches but had a highly significant effect on the variables of flowering age, number of pods, and net dry weight. The application of NPK Pearl professional 9-25-25 doses on red bean plants can be applied in lowlands, and the best dose from this study is 4 g/liter of water